Religion and Millennial Generation in Indonesia (Efforts to Develop Religious Character in Anticipation of the Negative Influences of Modernization in Indonesia) - Wahyuddin Wahyuddin (UIN Sunan Kalijaga Yogyakarta, 2019)
This article elaborated on the importance of religious character in anticipating the negative influences of modernization on religion in the millennial generation. Religious character is a character contained in the values of every religion adhered to by Indonesian people. Findings showed that religious character was significant in dealing with problems in the current millennial era. Social riots that were triggered from racist views and events of blasphemy can be overcome by promoting an inclusive, humanist and dialogical attitude. Every millennial generation in Indonesia must hold the values of the three attitudes and characters, especially in managing social, interreligious, ethnic, national and linguistic relations in order to create a peaceful life so that the goals of the country, namely welfare for every citizen regardless of religion, ethnicity, nation and race, can be achieved.[Artikel ini menguraikan tentang pentingnya karakter relijius dalam mengantisipasi pengaruh negatif modernisasi terhadap agama pada generasi milenial. Karakter relijius adalah karakter yang terkandung dalam nilai-nilai setiap agama yang dianut oleh masyarakat Indonesia. Temuan menunjukkan bahwa karakter relijius sangat penting dalam menangani masalah di era milenium saat ini. Kerusuhan sosial yang dipicu dari pandangan rasis dan peristiwa penistaan dapat diatasi dengan mempromosikan sikap inklusif, humanis dan dialogis. Setiap generasi milenial di Indonesia harus memegang nilai-nilai dari tiga sikap dan karakter tersebut, terutama dalam mengelola hubungan sosial, antar-agama, etnis, bangsa, dan bahasa untuk menciptakan kehidupan yang damai sehingga tujuan negara, yaitu kesejahteraan bagi setiap warga negara tanpa memandang agama, etnis, bangsa dan ras, dapat terlaksana.]